Exercises of dynamic stability under unstable conditions increase muscle strength and balance ability in the elderly. (6th February 2018) - Hamed, A.; Bohm, S.; Mersmann, F.; Arampatzis, A.
Abstract : The purpose of this study was to assess the effectiveness of a specific exercise intervention of mechanisms to control dynamic postural stability under unstable conditions in old adults. Forty‐seven old adults (65‐80 years) were assigned to 2 experimental groups (muscle strength group, n = 15; perturbation‐based group, n = 16) and a control group (n = 16). The strength group performed resistance exercises for leg and trunk muscles, while the perturbation‐based group exercised mechanisms of dynamic stability under unstable conditions. The training duration was 14 weeks, with training sessions twice a week for 1.5 hours. Muscle strength, balance ability, and balance recovery performance were investigated before and after the interventions using maximal isometric plantar flexion and knee extension contractions, the approach of the center of pressure to the anterior limits of stability and simulated forward falls. Both interventions increased balance recovery performance in simulated forward falls (81%, d  = 1.50 and 80%, d  = 1.08 in the muscle strength and perturbation‐based group, respectively), while the control group did not show any changes. Plantar flexor strength increased 20% ( d  = 0.72) in the muscle strength and 23% ( d  = 1.03) in the perturbation‐based group, while muscle strength of the knee extensors increased only in the muscle strength group (8%, d  = 0.76). On the other hand, only the perturbation‐based group showed a significant improvement of standing balance ability (38%, d = 1.61). We conclude that a perturbation‐based training program focusing on exercising mechanisms of dynamic stability in unstable conditions has the potential to enhance muscle strength as well as sensory information processing within the motor system during sudden and static balance tasks and, as a consequence, reduce the risk of falls in old adults.